Extremal solutions to a class of multivalued integral equations in Banach space. (1992) - Aizicovici, Sergiu; Papageorgiou, Nikolaos S.
Abstract : We consider a nonlinear Volterra integral inclusion in a Banach space. We establish the existence of extremal integral solutions, and we show that they are dense in the solution set of the original equation. As an important application, we obtain a bang-bang theorem for a class of nonlinear, infinite dimensional control systems.